Unlocking Knowledge with OCR-Driven Document Digitization for Peruvian Indigenous Languages - (:unkn) unknown (Association for Computational Linguistics (ACL), 2024)
The current focus on resource-rich languages poses a challenge to linguistic diversity, affecting minority languages with limited digital presence and relatively old published and unpublished resources. In addressing this issue, this study targets the di...
Keywords: Digitalización documental; Lenguas indígenas